2021
DOI: 10.1016/j.isci.2021.102699
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse AAV6 hACE2 transduction model of wild-type SARS-CoV-2 infection studied using synDNA immunogens

Abstract: More than 100 million people have been infected with SARS-CoV-2. Common laboratory mice are not susceptible to wild-type SARS-CoV-2 infection, challenging the development and testing of effective interventions. Here, we describe the development and testing of a mouse model for SARS-CoV-2 infection based on transduction of the respiratory tract of laboratory mice with an adeno-associated virus vector ( AAV6.2FF ) expressing human ACE-2 ( AAV6.2FF-hACE2 ). We validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…We interrogated the function of pADA-induced vaccine responses in an AAV6.2FF human ACE2 transduction model of SARS-CoV-2 infection in mice (8). In this model, we generated long-term expression of human ACE2 in the respiratory tract of wild-type mice, making them susceptible to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We interrogated the function of pADA-induced vaccine responses in an AAV6.2FF human ACE2 transduction model of SARS-CoV-2 infection in mice (8). In this model, we generated long-term expression of human ACE2 in the respiratory tract of wild-type mice, making them susceptible to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that transduction of the mouse respiratory tract with modified adeno-associated virus-6 (AAV6.2FF) results in robust transgene expression in the lung (13). Recently, we extended this work to model SARS-CoV-2 infection by expressing human angiotensin-converting enzyme-2 (hACE2) and demonstrated that this model supports replication of wild-type SARS-CoV-2 in the lungs of mice and provides an easily accessible experimental system with which to evaluate the efficacy of anti-SARS-CoV-2 vaccines and therapeutics (8). Using this model, we evaluated the effect of pADA coimmunization on the efficacy of our SARS-CoV-2 synDNA Ags.…”
Section: Ada-1 Enhances T Cell Monofunctionality and Polyfunctionalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we employed a SARS-CoV-2 pseudotyped lentivirus (also referred to as lentivirus particles) to determine the effectiveness of ACE2 gum in neutralizing spike-mediated viral infection. Lentiviral particles pseudotyped with the viral spike protein and harboring the pseudoviruses expressing a luciferase reporter gene were used to infect Chinese hamster ovary (CHO) cells expressing human ACE2 48. SARS-CoV-2 spike glycoprotein pseudotyped viruses expressing luciferase were incubated with ACE2 gum at the indicated concentration for 90 min at room temperature.…”
mentioning
confidence: 99%